2010
DOI: 10.1111/j.1540-6229.2010.00271.x
|View full text |Cite
|
Sign up to set email alerts
|

The Termination of Subprime Hybrid and Fixed-Rate Mortgages

Abstract: Adjustable‐rate and hybrid loans have been a larger component of subprime mortgage lending in the mortgage market than prime lending. The typical adjustable‐rate loan in subprime is a hybrid of fixed and adjustable characteristics in which the first 2 years are fixed and the remaining 28 years adjustable. Hybrid loans terminate at elevated probabilities even before the first adjustment date. Hybrid loan terminations are sensitive to interest rates and teaser rates (payment shocks). Default probabilities increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
54
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(58 citation statements)
references
References 21 publications
(24 reference statements)
4
54
0
Order By: Relevance
“…Yet the remaining sample statistics reveal other important differences between black and white borrowers that might plausibly account for racial disparities in lending terms and foreclosure rates. For example, blacks evince a greater likelihood of borrowing at the housing bubble's peak in 2006 as well as lower incomes, credit scores, and rates of neighborhood educational attainment, all factors that prior studies have shown to undermine loan performance and raise the odds of default and foreclosure (e.g., Anacker and Carr 2011; Chan et al 2013; Ding et al 2011; Gilderbloom et al 2012; Pennington-Cross and Ho 2010). …”
Section: Methodsmentioning
confidence: 99%
“…Yet the remaining sample statistics reveal other important differences between black and white borrowers that might plausibly account for racial disparities in lending terms and foreclosure rates. For example, blacks evince a greater likelihood of borrowing at the housing bubble's peak in 2006 as well as lower incomes, credit scores, and rates of neighborhood educational attainment, all factors that prior studies have shown to undermine loan performance and raise the odds of default and foreclosure (e.g., Anacker and Carr 2011; Chan et al 2013; Ding et al 2011; Gilderbloom et al 2012; Pennington-Cross and Ho 2010). …”
Section: Methodsmentioning
confidence: 99%
“…Some believe that low‐income homeowners are riskier borrowers in terms of default and prepayment; 4 others find that low‐ and moderate‐income borrowers have similar risk profiles and outcomes to higher income borrowers and are even sometimes less risky (Mills and Lubuele 1994, Calem and Wacther 1999, Van Order and Zorn 2002, Deng and Gabriel 2006). Finally, others research finds that loan performance in terms of default and prepayment can be as sensitive to the type of loan as it is the characteristics of the borrower (Ding et al 2011 and Pennington‐Cross and Ho 2010).…”
Section: Literature Review and Motivationmentioning
confidence: 99%
“…For example, the extra delay may come from the court when the court is overburdened, or from the borrowers when they contest the process or file for bankruptcy, from the requirement of the investor's guideline for loss mitigation effort (Cutts and Merrill ), or from third‐party servicers who have different incentives from the investors or the lenders (Levitin ). Pennington‐Cross and Ho () document that at an individual loan level, many factors could contribute to foreclosure duration.…”
mentioning
confidence: 99%